How Far Are NEET youth falling behind in their non-cognitive skills? An econometric analysis of disparities - Garen Avansesian; Marina Borovskaya; Marina Masych; Ludmila Dikaya; Victoria Ryzhova; Valeria Egorova (Economies, 2023)
Youth not in education, employment, or training (NEET) refers to the most vulnerable group in the transition from school to work. While much research focuses on institutional factors behind the NEET incidence, the current study approaches the problem of the NEET youth from the perspective of non-cognitive skills. For measuring non-cognitive skills, the Big Five personality characteristics (openness, conscientiousness, extraversion, agreeableness, neuroticism) as well as grit were analyzed. The analysis was carried out using propensity score matching based on the data of the Russian Longitudinal Monitoring Survey (RLMS HSE) for 2016. This study shows that the majority of young people in the NEET group come from the poorest families. Nearly half of the NEET youth are not only not working, but they are also not looking for a job either. The analysis revealed that NEET youth fall behind in different non-cognitive abilities, with statistically significant differences in conscientiousness, extraversion, and grit, as well as a greater severity of neuroticism.
Keywords: 330; NEET youth; non-cognitive skills; big five; labor market; education system